2006
DOI: 10.1002/bjs.5197
|View full text |Cite
|
Sign up to set email alerts
|

The role of cardiopulmonary fitness and its genetic influences on surgical outcomes

Abstract: Development of preoperative screening methods like cardiopulmonary exercise testing and genotype analysis to identify index factors may permit better patient stratification, provide targets for future tailored treatments and so improve surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 99 publications
0
17
0
Order By: Relevance
“…In addition to being a strong predictor of mortality in both asymptomatic and clinically referred populations, CRF level has been shown to be useful in predicting outcomes in the perioperative evaluation of patients undergoing bypass surgery, 61 abdominal aortic aneurysm repair, 62,63 bariatric surgery, 64 and other surgical interventions. 65,66 Higher CRF predicts lower mortality and lower rates of frailty and reliance on healthcare services at all age levels. 50 There is direct and growing evidence that an improvement in CRF over time has a considerable effect on lowering mortality.…”
Section: Importance Of Crfmentioning
confidence: 99%
“…In addition to being a strong predictor of mortality in both asymptomatic and clinically referred populations, CRF level has been shown to be useful in predicting outcomes in the perioperative evaluation of patients undergoing bypass surgery, 61 abdominal aortic aneurysm repair, 62,63 bariatric surgery, 64 and other surgical interventions. 65,66 Higher CRF predicts lower mortality and lower rates of frailty and reliance on healthcare services at all age levels. 50 There is direct and growing evidence that an improvement in CRF over time has a considerable effect on lowering mortality.…”
Section: Importance Of Crfmentioning
confidence: 99%
“…In this patient group it has been demonstrated that an AT of less than 11 mlO 2 .kg ) 1 .min )1 is predictive of an increased postoperative morbidity and mortality [4]. The AT measurement also provides valuable information to the patient about their individual risk assessment for a given procedure [5,6]. Medical optimisation prior to major noncardiac surgery is often employed to reduce peri-operative cardiorespiratory risk; however, the benefit of this is rarely assessed objectively.…”
mentioning
confidence: 99%
“…Preoperative evaluation: Postsurgery, oxygen demands are increased due to the accompanying hypermetabolism and hypercatabolism of the inflammatory stress response [70,71]. Oxygen demand increases by up to 50% in the immediate postoperative period [72], which necessitates a significant increase in CO and oxygen delivery [73].…”
Section: Respiratory Diseasementioning
confidence: 99%